THE EFFECT OF LIQUIDITY, LEVERAGE AND PROFITABILITY ON COMPANY VALUE - Dani Sopian; Dina Amellia Rohiati (ZILLZELL MEDIA PRIMA, 2023)
This research was conducted with the aim of determining the effect of liquidity, leverage and profitability on company value in property and real estate sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The population in this study was 85 companies. The sampling technique used was purposive sampling and obtained research samples of 22 companies. The analysis methods used are descriptive analysis and multiple linear regression analysis. The results showed that simultaneously liquidity, leverage and profitability have a positive and significant effect on the value of the company. And the test results partially show that liquidity has a positive and insignificant effect on the value of the company, leverage has a positive and significant effect on the value of the company, profitability has a positive and insignificant effect on the value of the company.